Study on the High-Birefringence Hollow-Core Anti-Resonant Fiber with Semicircular Cladding - Liu, Shuo; Li, Yuanwei; Ma, Rui; Zhao, Linwan; lv, Jiaqi; Dong, Xiaolong (International Journal of Optics, 2021)
For the purpose of satisfying the demands of polarization-maintaining fibers for fiber optic gyroscopes, this article proposes a semicircular cladding birefringent hollow-core anti-resonant fiber. The influence of structural parameters on the birefringence, loss, and bending loss of the fiber is studied. The simulation results demonstrate that at 1550 nm, the ultimate loss of the fundamental mode of x and y polarization is 1.76 dB/m and 0.93 dB/m, respectively. The birefringence can reach 1 × 10−4, and the wavelength range of birefringence greater than 10−4 can reach 60 nm. This indicates that it has excellent bending properties. The proposed optical fiber has excellent performance in polarization maintenance and can supply ideas for the research of high-precision fiber optic gyroscopes and other optical devices.